On the critical factors for estimating the pit stability product under a salt film - Wang, Ke; Salasi, Mobin; Bakhtiari, Sam; Iannuzzi, Mariano (ELECTROCHEMICAL SOC INC, 2021)
The pit stability product of 316L stainless steel (SS) under a salt film was examined by experimental techniques, analytical methods, and numerical modeling. Both analytical and numerical results suggested that electromigration had a measurable contribution to the dissolution current during stable pit growth under a salt film, preventing the use of the 1D Fick's law of diffusion to obtain the pit stability product under such conditions. Moreover, the numerical results indicated that migration contributed to almost ⅔ of the mass transport limiting current. Although the diffusion coefficient of metal cations decreased with an increasing concentration inside the pit, it could be replaced by a constant diffusion coefficient, defined as an equivalent diffusion coefficient. When the complexation reaction was cconsidered, the modeling results agreed with the experimental data, indicating that a 4.2 M FeCl2 could be used as a simplified pit-like electrolyte to estimate the pit stability product under a salt film for 316L SS.